Systematic pan-cancer analysis identifies APOC1 as an immunological biomarker which regulates macrophage polarization and promotes tumor metastasis - Liwen Ren; Jie Yi; Yihui Yang; Wan Li; Xiangjin Zheng; Jinyi Liu; Sha Li; Hong Yang; Yizhi Zhang; Binbin Ge; Sen Zhang; Weiqi Fu; et al. (Elsevier, 2022)
Apolipoprotein C1 (APOC1) has been found to play an essential part in proliferation and metastasis of numerous cancers, but related mechanism has not been elucidated, especially its function and role in tumor immunity. Through systematic pan-cancer analysis, we identified that APOC1 was closely associated with the infiltration of various immune cells in multiple cancers. Besides, APOC1 was significantly co-expressed with the immune checkpoints, major histocompatibility complex (MHC) molecules, chemokines and other immune-related genes. Furthermore, single-cell sequencing analysis suggested that the vast majority of APOC1 was expressed in macrophages or tumor-associated macrophages (TAMs). Additionally, the expression of APOC1 was significantly related to the prognosis of different cancers. Since APOC1 was most significantly abnormally expressed in renal cell cancer (RCC), subsequent experiments were carried out in RCC to explore the role of APOC1 in tumor immunity. The expression of APOC1 was significantly elevated in the tumor and serum of RCC patients. Besides, APOC1 was mainly expressed in the macrophage and it was closely related to the immune cell infiltration of RCC. Co-culture with RCC cells could induce the generation of TAMs with M2 phenotype which be blocked by silencing APOC1. The expression of APOC1 was elevated in the M2 or TAMs and APOC1 promoted M2 polarization of macrophages through interacting with CD163 and CD206. Furthermore, macrophages overexpressing APOC1 promoted the metastasis of RCC cells via secreting CCL5. Together, these data indicate that APOC1 is an immunological biomarker which regulates macrophage polarization and promotes tumor metastasis.